1979
DOI: 10.1128/jb.140.1.289-293.1979
|View full text |Cite
|
Sign up to set email alerts
|

Scanning electron microscope study of Saccharomyces cerevisiae spheroplast formation

Abstract: A suspension of Saccharomyces ceretisiae NCYC366 in buffered 1.2 M sorbitol containing Zymolyase-5000 (a ,/-glucanase-containing preparation) showed maximum osmotic sensitivity after 30 min of incubation at 30°C. A scanning electron microscope study of spheroplast formation, using a very high resolution (4-nm) machine, revealed several new morphological features. The surface of the plug in bud scars on intact cells appeared warty. The wall, which assumed a beady appearance as digestion proceeded, ultimately sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 20 publications
2
3
0
Order By: Relevance
“…Note that the border of the cell is surrounded by an artifactual structure resulting from the contact between the AFM probe and the pore edges. The cell surface is smooth and shows a ∼1 µm circular protrusion which can be attributed to a bud scar, in agreement with previous electron microscopy observations (Pringle et al , 1979; Koch and Rademacher, 1980). Note that birth scars were sometimes observed.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Note that the border of the cell is surrounded by an artifactual structure resulting from the contact between the AFM probe and the pore edges. The cell surface is smooth and shows a ∼1 µm circular protrusion which can be attributed to a bud scar, in agreement with previous electron microscopy observations (Pringle et al , 1979; Koch and Rademacher, 1980). Note that birth scars were sometimes observed.…”
Section: Resultssupporting
confidence: 91%
“…Previous cytological and chemical investigations have shown that the cell walls of S. cerevisiae consist primarily of a microfibrillar array of β1–3 glucans overlaid by an outer layer of β1–6 glucans and mannoproteins (Pringle et al , 1979; Fleet, 1991; Kreutzfeldt and Witt, 1991; Osumi, 1998). Accordingly, enzyme digestion studies have revealed that the cell wall is sensitive to protease (Zlotnik et al , 1984) and β‐glucanase (Fleet, 1991).…”
Section: Resultsmentioning
confidence: 99%
“…Similar features have been reported for fungal spores and bacterial cells . They can be ascribed to the stretching of flexible cell surface macromolecules, i.e., glucans and mannoproteins in the present work. , Interestingly, we also note that the mean rupture length was correlated with the adhesion force value, i.e., largest rupture lengths being observed at pH 4, suggesting that the adhesiveness of cell surface polymer chains may depend on their conformation.…”
Section: Resultssupporting
confidence: 89%
“…To minimize the risk of contamination by reusable equipment and maximize the fungal DNA yield from blood specimens containing small quantities of infecting fungus, we chose an enzymatic method of fungal cell wall disruption for the extraction procedure. ␤-1,3-Glucanase enzymes hydrolyze glucose polymers at ␤-1,3glucan linkages in fungi, releasing laminaryipentaose and resulting in fungal spheroplasts, which are modified organisms that have partially lost the cell wall and that have increased osmotic sensitivity (37). Until the 1970s, snail gut enzyme was the prototype enzyme used for fungal cell wall lysis, but the preparation had variable activity from batch to batch (26,27).…”
Section: Discussionmentioning
confidence: 99%